2018
DOI: 10.1186/s13047-018-0283-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a multicenter training programme to teach point‐of‐care vascular ultrasound for the detection of peripheral arterial disease in people with diabetes

Abstract: BackgroundThe primary aim of this study was to evaluate the effectiveness of a training programme to teach a focused bedside ultrasound scan (PAD-scan; Podiatry Ankle Duplex Scan) for the detection of arterial disease in people with diabetes.MethodsFive podiatrists and one diabetologist across two hospitals were enrolled in a structured training programme consisting of a training course (1-day), supervised scanning (5-weeks), independent scanning (3-weeks) and a final evaluation of performance (1-day).Time, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The implementation of PAD-scan in clinical practice necessitates training of front-line staff which can be effectively integrated into clinics. 10 An alternative model of care could involve PAD detection clinics being delivered by vascular scientists who would not require additional training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of PAD-scan in clinical practice necessitates training of front-line staff which can be effectively integrated into clinics. 10 An alternative model of care could involve PAD detection clinics being delivered by vascular scientists who would not require additional training.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that a focused DUS scan of the anterior and posterior tibial arteries at the ankle (PAD-scan; Podiatry Ankle Duplex scan; Figure S1-2, http://links.lww.com/SLA/ C885) can be readily learnt and accurately performed by frontline staff. 10,11 The primary aim of this present study is to determine the ability of the PAD-scan and other commonly performed index tests [handheld Doppler (audible and visual), ABPI, TBPI, TcPO2, and pulse palpation] to discriminate between the presence and absence of PAD in diabetes, as compared with the reference test of full lower limb arterial DUS.…”
mentioning
confidence: 99%
“…15,23,[25][26][27][28] For PAD-scan, in addition to equipment costs, costs of training were calculated based on a previous study. 11 This included additional costs related to ongoing training during the model period.…”
Section: Estimates Of Unit Costsmentioning
confidence: 99%
“…Data were collected as part of a previously published study exploring the effectiveness of a multi-centre training programme to teach focused DUS examination of the anterior and posterior tibial arteries at the level of the ankle for the detection of PAD in diabetes. 4 As part of the training programme, consecutive patients presenting to diabetic foot clinics at a teaching hospital in London and a district general hospital in London were invited to take part in the study and provided informed consent. A fully qualified vascular scientist performed the scan on each patient.…”
Section: Data Collectionmentioning
confidence: 99%